2020
DOI: 10.1097/won.0000000000000715
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Multilayered Polyurethane Foam Dressings to Prevent Hospital-Acquired Sacral Pressure Injuries in Patients With Hip Fracture

Abstract: PURPOSE: The purpose of this study was to determine the effectiveness of a multilayered polyurethane foam dressing applied within 24 hours of hospital admission compared with standard preventive pressure injury (PI) care in reducing sacral PI occurrence in older patients with hip fractures. DESIGN: Open-label, parallel-group, 2-arm, superiority trial. SUBJECTS AND SETTING: The sample comprised older patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…However, it is important to note that replacement of the dressing was often required before a routine change was due, most commonly due to the dressing lifting or rolling, or soiling from incontinence. Other trials have also reported similar issues 18,21. Our results suggest that routine dressing changes in an elderly population may be required more often than weekly, and dressings may need to be removed temporarily for some activities such as showering.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…However, it is important to note that replacement of the dressing was often required before a routine change was due, most commonly due to the dressing lifting or rolling, or soiling from incontinence. Other trials have also reported similar issues 18,21. Our results suggest that routine dressing changes in an elderly population may be required more often than weekly, and dressings may need to be removed temporarily for some activities such as showering.…”
Section: Discussionsupporting
confidence: 71%
“…Our results suggest that routine dressing changes in an elderly population may be required more often than weekly, and dressings may need to be removed temporarily for some activities such as showering. Indeed, while trials of the study dressing in different populations have reported following the same routine of dressing changes on a weekly basis unless required earlier13,21 and dressing changes as per manufacturer instructions,18 other trials with different dressings have performed changes more frequently (eg, every 3 days) 15,17,19…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 967 unique studies were identified, of which 11 studies (between 2015 and 2021) fulfilled the inclusion criteria and were included in this meta-analysis. [25][26][27][28][29][30][31][32][33][34][35] The 11 studies included 5150 community-or hospital-based adult subjects requiring care at the start of the study; 2832 of them were using sacral protective dressings and 2318 were given standard care with no sacral protective dressings. All studies evaluated the effects of prophylactic sacral protective dressings on preventing pressure injury.…”
Section: Resultsmentioning
confidence: 99%